Is there a Race-to-the-Bottom in the Setting of Welfare Benefit Levels? Evidence from a Policy Intervention - Matz Dahlberg; Karin Edmark (Uppsala University, Department of Economics, 2004)
In this paper we investigate whether local governments react on the welfare benefit levels in neighboring jurisdictions when setting their own benefit levels. We solve the simultaneity problem arising from the welfare game by utilizing a policy intervention; more specifically, we use a centrally geared exogenous placement of a highly welfare prone group (refugees) among Swedish municipalities as an instrument. The IV estimates indicate that there exists a race-to-the-bottom and that the effect is economically as well as statistically significant; if the neighboring municipalities decrease their welfare benefit level with 100 SEK, a municipality decreases its benefit level with approximately 59 SEK. This result is robust to several alternative model specifications.
Keywords: C33; D60; H73; 330; Welfare benefit level; Strategic interactions; Race-to-the-bottom; Policy intervention; Öffentliche Sozialleistungen; Gemeinde; Sozialpolitik; Spieltheorie; Schweden